Evaluation of Si̇vri̇hi̇sar’s Tourism Potential with SWOT Analysis within the Scope of Sustainable Tour - Dikmen, Çiğdem Belgin (Current Studies in Social Sciences VI, 2023)
The traditional urban texture of Sivrihisar has been significantly preserved with the contribution of its location and transportation opportunities. However, urbanization, changing lifestyles and increasing immigration threaten the sustainability of the traditional texture. Sivrihisar, which needs to be preserved and transferred to future generations with its natural beauties, historical and archaeological richness, monumental and civil architecture examples, handicrafts and gastronomic values hasn’t been promoted enough although it has an important potential in terms of tourism. This study aims to evaluate the tourism potential of Sivrihisar with SWOT analysis within the scope of sustainable tourism and to offer suggestions to improve it.